Aplikasi Penjadwalan Pengadaan Barang Menggunakan Algoritma Apriori pada Logistic Rumah Sakit - Sofyan Sofyan; Siti Nur Asia; Nasrun Nasrun (Universitas Darul Ulum, 2023)
The purpose of this study is to design an application for scheduling procurement of goods at the Logistics of Awal Bros Hospital Makassar and to apply the a priori algorithm for scheduling procurement of goods at the Logistics of Awal Bros Hospital Makassar. The results of this study are that based on application testing carried out on Gtmetrix, the results for pageSpeed Score 96% YSlow Score 90%, which means the program can function properly and based on program functionality testing with blackbox that the application is valid and can be applied. The conclusion of this research by applying the Apriori algorithm. This application displays the priority of procurement requests in the form of print and atk categories based on the categories of goods that are frequently requested and can display the scheduling of procurement of goods to restock goods by looking at the functions of the red, orange and green buttons on the application.